Co-Branding Dan Pengaruhnya Terhadap Brand Image - Pratama, Rommy; Widjajanta, Bambang; Razati, Girang (Universitas Pendidikan Indonesia, 2017)
The purpose of this study was to determine the effect of Credit Problems and Profitability. The methodology of this research was carried out in a period of five years, for ten banks, in the framework of the research design used was historical data, for non-random samples using historical data, the design of this study used pooled design. This study uses a descriptive and verification approach with hypothesis testing methods and data analysis techniques using panel data regression. The findings of this study are Credit Problems affecting Profitability. The difference is determined in the independent variables, objects and research methods, population and research samples, research period, measurement tools and research results, as well as sources of theory and foreign journals and foreign books and research results.